DESCRIPTION OF QUADRIGYRUS MACHADOI (FABIO, 1983) (ACANTHOCEPHALA, QUADRIGYRIDAE) IN NATIVE FISH OF WETLANDS ASSOCIATED WITH THE SAN JAVIER RIVER, SANTA FE, ARGENTINA - B. Chemes, Silvina (2013)
In order to study the host-parasite interaction of native fish Middle Paraná system, Santa Fe, Argentina, the digestive tracts of 64 specimens of Hoplias malabaricus (Pisces, Erythrinidae) and of 70 specimens of Pimelodus maculatus (Pisces, Pimelodidae) were analyzed. These native species are important for the economy and recreational activities of the region. The fish were collected from two lentic environments associated with the San Javier River, Cayastá, in the province of Santa Fe, Argentina. After dissecting the digestive tracts, parasites were detected by stereoscopic microscopy, collected and preserved in alcohol at 70% for subsequent taxonomic identification and description. In the intestines of both hosts, sixty-nine specimens of Quadrigyrus machadoi (Acanthocephala, Quadrigyridae) were reported for the first time in the Middle Paraná System in this province. The parasitic prevalence was determined for each case (P= 20.31 %, H. malabaricus; P= 28.6 %, P. maculatus) and an extended description of the icthyoparasite was carried out. This work broadens the geographical distribution of Q. machadoi for both hosts and contributes to the advancement of knowledge on the icthyoparasites associated with the regional icthyc fauna.